The Four-Equation New Keynesian Model - Sims, Eric; Wu, Jing Cynthia; Zhang, Ji (The Review of Economics and Statistics, 2023)
Abstract This paper develops a New Keynesian model featuring financial intermediation, short- and long-term bonds, credit shocks, and scope for unconventional monetary policy. The log-linearized model reduces to four equations: Phillips and IS curves, as well as policy rules for the short-term interest rate and the central bank's long-bond portfolio (QE). Credit shocks and QE appear in both the IS and Phillips curves. In equilibrium, optimal monetary policy entails adjusting the short-term interest rate to offset natural rate shocks but using QE to offset credit market disruptions. Use of QE significantly mitigates the costs of a binding zero lower bound.